Examining Demographic, Social-Emotional, and Educational Factors Influencing Teaching Motivation among Arab Teachers in Regular and Special Education - Zubeidat, Ihab (Journal of Ecohumanism, 2024)
In recent years, research has increasingly emphasized the emotional, social, and educational aspects of teacher training and professional practices in both regular and special education systems. This study aims to: (a) investigate differences in teaching motivation, socio-emotional learning, perceived social and family support, mental well-being, resilience resources, and situational anxiety across demographic variables (specifically gender, age, academic qualifications, and type of education system) among Arab teachers in northern Israel; and (b) assess the extent to which these socio-emotional and educational factors explain the variance in teaching motivation among these teachers. To achieve these objectives, teachers from both regular and special education settings were asked to provide demographic information and complete self-report measures targeting the specified factors. The results revealed significant differences in socio-emotional and educational factors across the demographic variables of gender, age, academic qualifications, and type of education system (regular or special education). Notably, a significant negative relationship was observed between teaching motivation and situational anxiety, while positive relationships were found between teaching motivation and perceived social and family support, mental well-being, socio-emotional learning, and resilience resources. Moreover, multiple linear regression analysis identified socio-emotional learning, mental well-being, and resilience resources as significant predictors of teaching motivation, accounting for approximately 35.3% of the variance. This study highlights the critical role of socio-emotional factors in shaping teaching motivation, particularly among Arab teachers in northern Israel. Understanding these dynamics can inform targeted interventions and support systems, ultimately enhancing teacher effectiveness and improving student outcomes in both regular and special education settings.